2003
DOI: 10.1007/s00428-002-0750-6
|View full text |Cite
|
Sign up to set email alerts
|

Pyloric gland adenoma: a clinico-pathological analysis of 90 cases

Abstract: Background: Pyloric gland adenoma is a rarely described neoplasia of the gastric mucosa. Recent publications have shown that similar lesions are also found in the gallbladder, the main pancreatic duct, the duodenum and the cervix of the uterus. Apart from case reports, few clinical data are available on these patients. We therefore conducted a search of the archived material collected between 1990 and 2000 for more clinical data on patients with this rare lesion. Patients and methods: Between 1990 and 2000, 90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
140
3
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(160 citation statements)
references
References 18 publications
12
140
3
5
Order By: Relevance
“…These lesions were fully characterized in 2003 by Vieth et al 19 and confirmed by our group. 18 As most histologic studies of upper tract lesions in FAP patients were published before the recognition of PGAs, these lesions were presumably classified as other types of polyps in previous reports.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…These lesions were fully characterized in 2003 by Vieth et al 19 and confirmed by our group. 18 As most histologic studies of upper tract lesions in FAP patients were published before the recognition of PGAs, these lesions were presumably classified as other types of polyps in previous reports.…”
Section: Discussionsupporting
confidence: 77%
“…These polyps show a preference for the gastric body, and gastric examples show a remarkable female predominance. This female predominance occurs because many PGAs arise in patients with autoimmune metaplastic atrophic gastritis, 18,19 which characteristically has ample pyloric metaplasia. In one study of gastric polyps in 461 patients with autoimmune gastritis, 143 patients had endoscopically identifiable lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, a direct morphological comparison of sporadic and FAP associated PGAs could not be performed. However, it is felt that our group is well equipped to compare our findings in PGAs in FAP to the existing literature on sporadic pyloric and oxyntic gland adenomas since several authors of the current study significantly contributed to this field 1, 35, 9, 15, 17, 18 . Unfortunately previous studies on PGAs in FAP did provide extensive morphological assessment of these polyps 3, 7 …”
Section: Discussionmentioning
confidence: 88%
“…Pyloric gland adenomas consist of proliferations of closely packed tubules, each lined by a monolayer of round basally oriented nuclei with apically oriented eosinophilic ground glass cytoplasm [1921 ]. They are most commonly detected in the stomach, where they are likely to arise in patients with autoimmune gastritis.…”
Section: Discussionmentioning
confidence: 99%